Assessing the effect of selection tools as a predictor of employee performance: A case study of Ghana Revenue Authority, Kumasi - Mensah Foah, Abena (2015)
A thesis submitted to the Department of `Managerial Science, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the Degree of MASTERS OF BUSINESS ADMINISTRATION (HUMAN RESOURCE MANAGEMENT).